Southeast Asia Track II Diplomacy: The Role of ASEAN-ISIS in ASEAN Community Building - Thiparat, Pranee (Political Science Critique, 2026)
This article pursues three objectives. First, it provides an overview of the origins and evolution of Track II diplomacy in Southeast Asia over nearly four decades, focusing in particular on the institutional network of ASEAN-ISIS (the ASEAN Institutes of Strategic and International Studies). Second, it examines and assesses the policy role that ASEAN-ISIS has played as a think tank—one that has exerted a distinctive and tangible influence from its founding in 1988 to the present. The discussion centers on how the network has supported and advanced the work of ASEAN as a regional intergovernmental organization, whether through its initiatives, its policy proposals, or its constructive engagement in forums convened to debate security challenges and ASEAN’s adaptation to strategic shifts in the region, particularly in the post–Cold War era. Third, it analyzes the achievements, limitations, and future trajectory of ASEAN-ISIS against the backdrop of geopolitical change across Asia and the Indo-Pacific. In doing so, it considers the proliferation of Track II institutions—both in number and in thematic breadth—at the level of individual ASEAN member states and across the wider Asia-Pacific, together with the growing role of civil society, in order to ask whether, and in what ways, these developments bear on the operations and future relevance of ASEAN-ISIS.